Skin and Colon Cancer Media Campaigns in Utah - Camille Broadwater; Janet Heins; Catherine Hoelscher; Adam Mangone; Cami Rozanas (Centers for Disease Control and Prevention, 2004)
The mission of the Utah Cancer Action Network is to reduce cancer incidence and mortality in Utah. Established in 2003, the network selected skin and colon cancers as the first priorities in its comprehensive plan. In its first year of operation, the network planned and implemented a cancer awareness campaign that was organized along two tracks: 1) marketing research, consisting of two telephone surveys, and 2) two advertising/awareness campaigns, one for colon cancer and one for skin cancer. The first telephone survey was conducted in January 2003 to obtain a baseline measurement of the Utah populations knowledge, attitudes, and behaviors. The advertising campaigns were launched in April 2003, and the second telephone survey was conducted in May. In January 2003, 18% of survey respondents reported seeing or hearing skin cancer prevention or sun protection announcements; in May, this percentage increased to 76%. In January, 36% indicated they had seen, read, or heard colorectal cancer early detection announcements; in May, this percentage increased to 79%.